P84 The impact of a multidisciplinary educational programme on the prescribing of oxygen in an acute trust. (16th November 2010) - Khachi, H; Burman, M; Walters, L; Sinha-Ray, R; Antoniou, S; Mandal, S
Abstract : Introduction and objectives: Following the publication of the BTS guideline1 and NPSA rapid response report2 on the use of oxygen, a multidisciplinary educational programme was developed to improve the prescription of oxygen in a large London teaching hospital. The aim of this project was to assess the impact of the educational programme. Methods: Following a baseline audit of oxygen prescribing, posters were introduced to promote and improve the prescription of oxygen. A second audit demonstrated that no improvement in adherence to guidelines had occurred. In response to this, a Trust wide oxygen policy, development of an oxygen sticker and a comprehensive multi-disciplinary educational programme was delivered, aimed at all medical, nursing, physiotherapy and pharmacy colleagues. The programme involved a series of practical sessions and presentations tailored to each discipline and delivered by pharmacy, physiotherapy and medical representatives. To assess the impact of the interventions, prospective data was collected assessing patients on oxygen against the following criteria: Has oxygen been prescribed? If so, have the following been indicated: Target saturations Starting device and flow rate Continuous or when required oxygen Signed and dated by doctor Nurse signature for administration Clinically screened by pharmacist Results: The baseline audit demonstrated that oxygen was prescribed in only 23% of cases, of these 50% had target saturations prescribed. All those with an oxygen prescription had regular saturations and administration of oxygen recorded. Re-audit following introduction of educational posters demonstrated only 6% of patients had oxygen prescribed and target saturations documented (n=1). On delivery of the educational programme, a further audit recruited 563 patients, of which 83 patients (15%) were administered oxygen, 30 (36%) had oxygen prescribed appropriately, 73% with target saturations and 77% of which used the newly designed oxygen sticker (Abstract P84 Table 1 ). Conclusions: We have demonstrated that when changing clinical practice educational posters alone were not effective, however, a structured multidisciplinary teaching programme improved the prescription of oxygen to above national standards. Whilst further improvement is required, a rolling educational programme may further support this.